Computing the number of distinct fuzzy subgroups for the nilpotent p-group of D2n x C4. (2020)
In this paper, the explicit formulae is given for the number of distinct fuzzy subgroups of the cartesian product of the dihedral group of order 2n with a cyclic group of order four, where n > 3.